Cognitive dimensions of orthographic stimuli affect occipitotemporal dynamics - Wilson, Tony W.; Leuthold, Arthur C.; Lewis, Scott M.; Georgopoulos, Apostolos P.; Pardo, Patricia J. (Experimental brain research, 2005)
Previous research documented letter-string specific cortices in the ventral visual stream near the left occipitotemporal junction (i.e., anterior fusiform gyrus). These neural areas potentially code the perceptual elements comprising orthographic stimuli, and thus function as feature detectors in high-level vision. While abundant evidence supports this region's role in detecting isomorphic perceptual features, any influence cognitive dimensions (e.g., the lexicality of letter-strings) may play in modulating this area's processing remains an open question. To investigate this, we examined the spatiotemporal dynamics of high-density magnetoencephalographic signals, recorded as subjects completed a rhyme-judgment task on stimuli varying in the cognitive property of lexicality. Our data demonstrate that the time course of occipitotemporal cortices discriminates cognitive attributes of orthographic stimuli. The dynamics in this brain region may indicate interactive processes unfolding later in the time course, when more anterior fronto-temporal circuits are activated by semantic correlates of real words.